الحرب النفسية والحرب النفسية المضادة بين فرنسا والثورة الجزائرية - باي,أسماء; شايع,صفية (University of Eloued جامعة الوادي, 2024)
تتناول هذه الدراسة محطات الحرب النفسية" و "الحرب النفسية المضادة، التي دارت رحاها بين المحتل الفرنسي وثورة التحرير الجزائرية طيلة فترة الثورة، من 01 نوفمبر 1954م إلى غاية 05 جويلية 1962م مستندة إلى الأهداف التي خطها كلا الطرفين للتحقيق مرراً بالآليات المعتمدة، والنتائج المحققة مع استعراض الأسس التي أقام عليها كل طرف إدارة حربه، وأيهما كانت أسسه أبلغ في تحقيق النتائج.. . This study deals with the phases of psychological warfare and counter-psychological warfare that took place between the French occupier and the Algerian liberation revolution throughout the period of the revolution, from November 1, 1954 AD until July 5, 1962 AD, based on the objectives set by both parties for investigation, including the approved mechanisms, and the results achieved with Reviewing the foundations upon which each party established its war management, and whichever foundation was more effective in achieving results.
1954-1962 م
Keywords: الحرب النفسية; جبهة التحرير الوطني; الحرب النفسية المضادة; psychological warfare; the French occupation; The Algerian Revolution